Intestinal malrotation with concurrent duodenal duplication cyst in a 1-day-old infant - Derek R. Marlor; Hunter Freisen; Khaled M. Taghlabi; Nelimar Cruz Centeno; Kurt Schropp (Elsevier, 2022)
Congenital intestinal malrotation and duodenal duplication cysts are congenital anomalies that are present during the neonatal period. The presence of both in a single patient is exceedingly rare with limited similar case reports present in the literature. We present the case of a neonate diagnosed with a right-sided ovarian cyst in utero, who was later found to have a concurrent duodenal duplication cyst and intestinal malrotation. Treatment consisted of open Ladd's procedure, resection of duplication cyst, and primary duodenoduodenostomy. The report serves as a data point for this rare phenomenon as well as provides surgical options for similar cases.